2015
DOI: 10.1016/j.jascer.2014.10.006
|View full text |Cite
|
Sign up to set email alerts
|

The effect of B4C particle size on the reaction process and product in the Cu–Zr–B4C system

Abstract: ZrC and ZrB 2 were prepared by self-propagating high-temperature synthesis in a Cu-Zr-B 4 C system. We explored the influence of B 4 C particle size on the reaction process, phase composition and microstructure of the products. The results show that the production of ZrC and ZrB 2 is mainly controlled by the dissolution of B 4 C in Cu-Zr liquid. Increasing the size of B 4 C will not affect the reaction path, but will retard the formation of the Cu-Zr-B-C liquid. This leads to the incomplete conversion of ZrC a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 21 publications
(27 reference statements)
1
9
0
Order By: Relevance
“…It is notable that the diffraction peak of B 4 C is far weaker than Zr or it cannot be detected though the mole percentages of B 4 C and Zr are 25% and 75%, respectively. Similar phenomena also existed in the Cu-B 4 C [20] and Co-B 4 C systems. The relative diffraction intensity formula of phase in the powder mixtures can be described as follows:…”
Section: Dsc Experimentssupporting
confidence: 68%
See 1 more Smart Citation
“…It is notable that the diffraction peak of B 4 C is far weaker than Zr or it cannot be detected though the mole percentages of B 4 C and Zr are 25% and 75%, respectively. Similar phenomena also existed in the Cu-B 4 C [20] and Co-B 4 C systems. The relative diffraction intensity formula of phase in the powder mixtures can be described as follows:…”
Section: Dsc Experimentssupporting
confidence: 68%
“…Therefore, increasing B concentration in the Co-Zr-B-C liquid may restrain the presence of Co 2 B or/and ZrCo 3 B 2 in the CS products. In a previous work [20], the effect of B 4 C particle size on the CS process and product in the Cu-Zr-B 4 C system was investigated. Research results showed that increasing B 4 C size will reduce the dissolution rate of B 4 C in Cu-Zr liquid and lead to the incomplete conversion of ZrC and ZrB 2 .…”
Section: Combustion Wave Quenching Experimentsmentioning
confidence: 99%
“…The results of the X-ray phase analysis revealed no traces of the starting B 4 C among the products of interaction, indicating the completeness of the reaction course. Similarly, the course of the self-propagating high-temperature synthesis in the Cu-Zr-B-C system produced the particles of ZrB 2 and ZrC in the copper matrix [11]. The in situ formed VB 2 and (Ti,V)B 2 were found by the authors of [12] when obtaining the B 4 C-based composites, by the hot-pressing method involving the powders of B 4 C, TiH 2 , and VC at 2,200 °C.…”
Section: Literature Review and Problem Statementmentioning
confidence: 99%
“…Our analysis of the scientific literature reveals that the main issue in the formation of coatings based on iron strengthened by Mo x B y in the form of separated inclusions, similar to TiB 2 [6][7][8][9], is the interaction within the Fe-Mo x-B y system. Its result is the formation of a FeMo 2 B 2 phase, which is part of the eutectics with iron, thereby forming a structure that is not optimal in terms of wear resistance, compared to composite [11][12][13]. Therefore, the conventional methods of hardfacing involving electrode materials in the form of master alloys or ferroalloys, which imply the complete melting and recrystallization of the alloy, are not rational for coatings from the Fe-Mo x B y system.…”
Section: Literature Review and Problem Statementmentioning
confidence: 99%
“…4,5) More recently, Yang et al 6) and Zhan et al 7) succeeded in synthesizing Ti(C,N)-TiB 2 composite ceramics through a one-step process of self-propagating high-temperature synthesis (SHS); however, this left a large number of pores in the resulting product. [6][7][8][9] There is, therefore, a need to nd a way of imposing additional pressure in order to improve the relative density of these ceramics.…”
Section: Introductionmentioning
confidence: 99%